Molecular characterisation and evolutionary analysis of Papaya ringspot virus infecting papaya (Carica papaya L.) - Swati, B; Chinnakaruppan, M; Niranjana, PMP; Yogita, M; Susheel, K; Vijayanandraj, S (Plant Science Today, 2026)
Papaya (Carica papaya L.) is a tropical, commercial fruit with high nutritive and medicinal value. Papaya ringspot virus (PRSV) causes destructive disease in papaya and cucurbit cultivation worldwide. The current study analysed the genetic diversity and phylogenetic relationship of 115 PRSV isolates submitted until December 2024 in NCBI, including one complete genome sequences from Palampur, India characterized in this study. The complete genome of a PRSV Palampur isolate collected during March 2020 from foothills of Himalayan region in northern India was characterized. The Palampur isolate (MW030522.1) showed close identity of 90 % with Bangladesh isolate (MH397222). Species demarcation analysis of nucleotide sequence revealed one major peak ranging between 79–85 %. The nucleotide diversity of the PRSV genome was 0.13. The 5’ end of the genome containing the P1 gene showed high levels of polymorphism. Phylogenetic analysis showed 4 major groups (G1-G4) and one recombinant isolate (MH444652). The results suggest that the geographic region, rather than hosts, is the probable factor determining the genetic diversity of PRSV isolates. Neutrality tests and dN/dS ratio showed negative values, indicating purifying selection. The current study deepens understanding of PRSV genetic diversity and evolution, which can be used for development of effective management strategies against PRSV.